2022
DOI: 10.1039/d2ra01216b
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical exploration of mechanical, electronic structure and optical properties of aluminium based double halide perovskite

Abstract: M2AgAlX6 (M = Cs, Rb and K, X = Cl, Br and I) is a stable vacancy ordered double halide perovskite direct band gap semiconductor material with good absorption of near-ultraviolet and short-wavelength visible light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 76 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…Typically, perovskite structures are more likely to form within the range of 0.8 t 1.0. Moreover, perovskite structures with a tolerance factor in the range of 0.9-1.0 tend to exhibit a more perfect and stable structure [50][51][52][53]. Here for this material, the tolerance factor is 1.…”
Section: Structural Propertiesmentioning
confidence: 91%
“…Typically, perovskite structures are more likely to form within the range of 0.8 t 1.0. Moreover, perovskite structures with a tolerance factor in the range of 0.9-1.0 tend to exhibit a more perfect and stable structure [50][51][52][53]. Here for this material, the tolerance factor is 1.…”
Section: Structural Propertiesmentioning
confidence: 91%
“…The imaginary part of the dielectric function ε 2 (ω) depicts the electron transitions from occupied to unoccupied states and is determined using the optical matrix element. In contrast, the real part of the dielectric function ε 1 (ω) is calculated by using the Kramers-Kronig relation [53]. To address the well-known underestimation of the standard GGA functional energy, we implemented the scissor operator ∆ = 1.41 eV for all-optical spectra.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…This increase can be attributed to the interactions between alkali ions and oxygen ions, highlighting the crucial role of alkali ions in the anion site (X site) interaction for determining band gap properties in perovskites . Additionally, Tang et al demonstrated that substituting the X site in Cs 2 AgAlX 6 double perovskite systems significantly affects the band gap, with a notable reduction observed in the sequence of Cl, Br, and I . This indicates that halogen anions exert a greater influence on the band gap value compared to alkali metals.…”
Section: Introductionmentioning
confidence: 99%
“…37 Additionally, Tang et al demonstrated that substituting the X site in Cs 2 AgAlX 6 double perovskite systems significantly affects the band gap, with a notable reduction observed in the sequence of Cl, Br, and I. 38 This indicates that halogen anions exert a greater influence on the band gap value compared to alkali metals.…”
Section: Introductionmentioning
confidence: 99%